The pardoner’s prologue & tale from the Canterbury tales - Chaucer, Geoffrey (Cambridge University Press, 1994)
This well-established series is now being updated with new scholarly introductions and attractive new covers. Texts are in the original Middle English throughout, and each has an introduction, detailed notes and a glossary.